The Role of E-Wallets, Service Quality, and Social Entrepreneurship in Enhancing Business Competitiveness - Prastyawan, Ayub; Puspaari, Ernita Dian; Windhyastiti, Irany; Khouroh, Umu; Irany Windhyastiti (Journal of Entrepreneurship and Business, 2024)
Purpose: This paper investigates the impact of using e-wallets, service quality, and social entrepreneurship on the competitiveness of MSMEs participants. Method: This study used a sample of 105 respondents who were active members of MSMEs in Sukun Market. These respondents ranged in age from 17 to 72 years old, indicating a broad spectrum of age groups and experiences, which provides a broad understanding of the demographic involved in MSMEs within this area. The method employed in this research included validity and reliability tests to examine the research instrument: a questionnaire, determination coefficient (R-Square), F-Square testing, and hypothesis testing. The testing was conducted using simple regression analysis. Result: The result of the study indicates that the use of e-wallets, service quality, and social entrepreneurship has a 66 percent influence on the competitiveness of MSMEs participants. Therefore, the variables have a positive and significant effect on the competitiveness of MSMEs participants in Sukun Market, Tanjungrejo Village, Malang City.